Building an online indigeous knowledge Library on culture, Environment and History: Case Study of Elimu Asilia - Owano, Ashah (National Museums of Kenya, 2016)
Kenyan libraries and information centres are inadequately equipped with local indigenous knowledge (IK) content to contribute to global digital knowledge economy. Scarcity of community stories and information on the web undermines the role of librarians and other information workers, denying local communities opportunity to participate in the development of local content about their communities and encourage them to use and appreciate local library services. All over the world, indigenous knowledge has been recognized as distinct, legitimate, valuable and vulnerable system of knowledge that requires appropriate skills to handle and manage. In Kenya, like most African countries, events and accounts were transmitted orally from one generation to another. The data/information was hardly documented. This paper presents a case study of ‘Elimu Asilia’, a participatory platform for developing local content where National Museums of Kenya librarians working with researchers and volunteers interact with local communities including children in the collection, preparation, preservation, sharing, exchange and dissemination of IK on culture, environment and history for memory, national sustainability and eco-social development using information communication technologies. It is envisaged that this platform will contribute towards the reduction of digital divide, sharing of community IK and promote global online communities for indigenous knowledge.